Effect of Keratocyte Supernatant on Epithelial Cell Migration and Proliferation After Corneal Crosslinking (CXL). (2nd April 2016) - Wu, Ming-Feng; Stachon, Tanja; Wang, Jiong; Song, Xuefei; Colanesi, Sarah; Seitz, Berthold; Wagenpfeil, Stefan; Langenbucher, Achim; Szentmáry, Nóra
Abstract: Purpose : To evaluate the effect of keratocyte supernatant (harvesting time, riboflavin concentration and UV-A-light illumination) on migration and proliferation of human corneal epithelial cells (HCECs) by CXL, in vitro . Methods : Primary human keratocytes isolated from 8 normal and 6 keratoconus corneas were cultured. Thereafter, keratocytes in 0%, 0.05% or 1% riboflavin solution were split into samples without and with 370 nm UVA-light-illumination. After removal of the riboflavin solution, keratocytes were incubated in the mentioned keratocyte culture medium at 37 °C and keratocyte supernatant was harvested after 5 and 24 hours. Keratocyte supernatant without riboflavin and UVA treatment, was used as control. HCECs were cultured until reaching confluence, the HCEC culture medium was replaced by the keratocyte supernatant and HCEC migration was analyzed using the wound-healing assay. HCEC proliferation was determined by the cell proliferation ELISA BrdU (colorimetric) kit. Statistical analysis was performed using a linear mixed model in the framework of a Generalized Estimating Equations (GEE) approach to analyze the effect of harvesting time, riboflavin concentration and UV-A-light illumination using IBM-SPSS version 22. Results : Riboflavin concentration, UVA-light illumination and harvesting time of normal or keratoconus keratocyte supernatant had no significant impact on HCEC proliferation ( p  > 0.10). Riboflavin concentration did not show significant impact on HCEC migration using normal or keratoconus keratocyte supernatant ( p  > 0.10), however, longer harvesting time of normal or keratoconus keratocyte supernatant significantly increased ( p  = 0.01 for both) and UVA-light illumination of keratoconus keratocyte supernatant ( p  < 0.001) significantly decreased HCEC migration. Conclusion : Harvesting time, riboflavin concentration and UV-A-light illumination of normal and keratoconus keratocyte cultures has no impact on proliferation of HCECs, in the short term. However, 24 hours harvesting time (both for normal and keratoconus keratocytes) increases and UVA-light-illumination of keratoconus keratocyte cultures decreases HCEC migration.